TRANSFORMATIVE EDUCATION AS A DIALECTIC OF INDONESIAN CULTURE AND MODERN CULTURE - Rochmat, Saefur (Jurnal Cakrawala Pendidikan, 2018)
Abstract:Indonesia has being an independent state more than 73 year, but it is not yet a modern state. It is due to a lack of continuity between Indonesian culture (in the forms of local cultures and religions) and modern culture. National culture, in the form of Pancasila state, is not similar to the original Indonesian culture as it is a mix of Indonesian culture and modern culture. This article is to elaborate transformative education which will synergize Indonesian culture and modern culture.This article is a kind of qualitative research, using observation and literature study methods. It focuses on the immaterial aspects of culture, namely supra-structure of both Indonesian culture and the modern one. Curriculum 2013 Revised that discards religious skills from all subjects, except Religious Education and Civic Education, reflects that government has not yet formulated clearly the national education system. National education should be transformative that enables to synergize the Indonesian culture to the modern one. Keywords:Indonesian culture, modern culture, religious skills, Pancasila PENDIDIKAN TRANSFORMATIF SEBAGAI DIALEKTIKA KEBUDAYAAN ASLI DENGAN KEBUDAYAAN MODERN Abstrak:Setelah merdeka lebih 73 tahun, Indonesia masih belum menjadi negara modern.Hal itu terjadi karena adanya kesenjangan antara kebudayaan lama dengan kebudayaan modern. Kebudayaan nasional dalam bentuk kebudayaan Pancasila tidak sepenuhnya merupakan kelanjutan kebudayaan asli sehingga Indonesia harus melakukan transformasi budaya. Artikel ini akan membahas pendidikan transformatif, yang akan mendialektikakan kebudayaan asli dengan kebudayaan modern.Artikel ini merupakan hasil penelitian kualitatif, yang dilakukan dengan metode observasi dan studi pustaka. Penelitian ditekankan pada aspek immaterial (suprastruktur), yang menjadi fondasi bagi struktur kebudayaan, baik dalam kebudayaan Indonesia maupun kebudayaan modern. Pendidikan transformatif merupakan pendidikan yang mampu mensinergikan suprastruktur kebudayaan asli (kebudayaan daerah dan agama) dengan suprasturktur kebudayanaan modern. Aspek suprastruktur kebudayaan asli tercermin dalam sila ke-1 yang bersifat religius, sedangkan aspek suprastruktur kebudayaan modern tercermin dalam sila ke-2, 3, 4, dan 5 yang sifatnya rasional. Kedua karakteristik ilmu itu harus menyatu dalam materi pelajaran yang diajarkan di sekolah, yang tercermin dalam religious skills. Kata kunci: kebudayaan asli, kebudayaan modern, religious skills, Pancasila